ISLAMIC ECONOMIC VIEW ON THE CONCEPT OF PAY LATER IN ONLINE SHOPPING MEDIA - Khairunnisa, Azizah; Suwandi, Intan; Shandy, Akhmad; Atami, Novi Amalia; Khairani, Mutia (Proceeding International Seminar of Islamic Studies, 2024)
This research analyzes and determines the consumption behavior of Indonesian people through the online shopping payment system method from an Islamic economic perspective. This research was conducted using a quantitative survey method by analyzing respondents' responses to surveys distributed via Google Form through a data analysis process, because the method used by researchers will reveal what the data experienced is based on the authenticity of the information expressed in the case. respondents . The findings show that from an Islamic economic perspective, the legality of a payment system depends on its use, whether it is detrimental or not. It can be said that the Paylater system is haram if it contains things that are prohibited by Allah SWT such as usury, jalal and so on. However, if the payment system provides benefits, is relevant to the Islamic economy, and does not contain detrimental elements such as usury, then the law is permissible.